Photovoltaic energy: analysis of production costs in a dairy in Minas Gerais, Brazil - Bassotto, Leandro Carvalho; do Nascimento, Rogério Max Ferreira; Lopes, Marcos Aurélio [UNESP]; Lopes Filho, Marcos Aurélio; de Benedicto, Gideon Carvalho; Tavares, Mateus Porreca (Centro Universitario de Maringa, 2022)
Dairy cattle is an important sector in Brazilian economy and its sustainability may contribute towards the development of the production chain. There are few studies that investigate the effects of the use of environmentally correct technologies in the administration of dairy costs. The economic and financial feasibility for the implantation of a small photovoltaic plant and the profitability of a dairy in the northern region of the state of Minas Gerais, Brazil, are analyzed. Operational and total costs were employed to investigate its profitability. The installation of a small photovoltaic plant on the dairy premises was financially feasible due to the fact that positive net value (R$ 711.77) and return internal rate (2.68%) were slightly lower than minimum attractivity rate (2.75%). Payback time (8 years and 8 months) was lower to the plant´s useful life. The photovoltaic plant reduced variable costs and was economically and financially feasible. It contributed towards an increase in crude and net profits and in the results (profit) of the dairy.
Energia fotovoltaica: análise de custos de produção em propriedade leiteira de Minas Gerais
Keywords: Agribusiness; Analysis of profit; Milk production; Solar energy; Sustainability